CORPORATE SOCIAL RESPONSIBILITY ON THE GLOBAL STAGE: A LEGITIMACY EXAMINATION IN EMERGING MARKETS - Antaresta Purwanto, Nathaniel (PEOPLE: International Journal of Social Sciences, 2024)
Prior research suggests that emerging market multinationals (EMNEs) increasingly adopt corporate social responsibility (CSR) as a tool to gain legitimacy abroad. Although many scholars have investigated the relationship between CSR and Internationalization to be positive, a number of factors that influence the relationship have been continuously studied in recent years. To examine the CSR-Internationalization relationship in the context of EMNEs, it is necessary to take a different theoretical approach than for developed market multinationals. Building on stakeholder theory, this thesis investigates the effect of CSR on the Scope of Internationalization of EMNEs including the moderating effect of host market development level and state ownership. To address this research question, I performed a multiple linear regression analysis on a sample of 105 EMNEs. Based on this theoretical approach, I predict a positive relationship between CSR and Internationalization and a positive moderating effect of host market development level and state ownership on that relationship. The findings of this thesis conclude that CSR has a significant positive effect on the scope of internationalization, while the effect of host market development level and state ownership remains unclear and insignificant. It sheds light on the importance of considering non-economic factors in understanding the international expansion of firms from emerging markets.